Pengaruh Insider Ownership, Collateralizable Assets, Growth In Net Assets, dan Likuiditas terhadap Kebijakan Dividen pada Perusahaan Manufaktur yang Listing di Bursa Efek Indonesia Periode 2002-2006 - Wahyudi, Eko; Baidori, Baidori (Universitas Brawijaya, Indonesia, 2008)
The research of this influence insider ownership, collateralizable assets, growth in net assets and liquidity on dividend policy is purposed to kwon the influence insider ownership, collateralizable assets. growth in net assets and liquidity (quick ratio) on dividend policy. The conclusion of this research is shown that simultanly insider ownership, collateralizable assets, growth in net assets and liquidity (quick ratio) influence significantly on dividend policy with determination coefisient 95,76% (Adjusted R2). Insider ownership partially influence not significantly on dividend policy and collateralizable assets, growth in net assets, and liquidity (quick ratio) influence significantly on dividend policy.